ANALISIS PINJAMAN BERMASALAH (LAR) TERHADAP RETURN ON INVESTMENT (ROI) UPK BUNGA TANJUNG PADA PINJAMAN BERGULIR PROGRAM KOTATANPA KUMUH (KOTAKU) DI DESA TANJUNG BARU KECAMATAN BATURAJA TIMUR - Zulkarnain, Zulkarnain; Bramana, Sally Maria (Universitas Indo Global Mandiri Palembang, 2020)
This study aims to determine whether the problem loans (LAR) affect the Return on Investment (ROI) UPK Bunga Tanjung on the Loans without Slums City Program (KOTAKU) in Tanjung Baru Village, East Baturaja District. The method used in this research is descriptive method. By using qualitative and quantitative data analysis techniques. The results obtained by the ratio of problem loans (LAR) UPK Bunga Tanjung in the Revolving Loans of the City without Slums Program (KOTAKU) in Tanjung Baru Village, East Baturaja Subdistrict always increase with an average ratio of 15.53%. While the Return On Investment (ROI) ratio always decreases with an average ratio of 10.15%. Non-performing loans (LAR) greatly affect the level of Return On Investment (ROI) in revolving loans UPK Bunga Tanjung Without Slum City Program (KOTAKU) in Tanjung Baru Village, East Baturaja District in 2014-2018. A small level of non-performing loans will benefit the UPK and conversely a high level of problem loans will reduce the profitability of the UPK.Â Keywords: Non-performing Loans (LAR), Return On Investment (ROI), Slumless City Program (KOTAKU).